The Effect Of Repeat Training Methods On Increasing Passing Results Parts In Football - Alchonity Harika Fitri; Ambiyar; Ishak Aziz (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
This study aims to identify and understand the effect of repeat training methods on increasing passing results parts in football. The type of research is experimental, with the design of this study using a quasi experiment with a one group pretest-posttest design. The population was the students of SMA Unggul Dharmasraya West Sumatra. Data collection was done by conducting pre-test and post-test passing accuracy of the students. Based on the results of calculations that have been carried out, a significant value of 2.01 1,000 is obtained. Thus, the hypothesis states that there is a significant difference in the effect of repetition training on improving the inner foot passing of football of SMA Unggul Dharmasraya West Sumatra, which is acceptable.